Nuclear protein FNBP4: A novel inhibitor of non-diaphanous formin FMN1-mediated actin cytoskeleton dynamics - Das, Shubham; Das, Saikat; Maity, Amrita; Maiti, Sankar (The Journal of biological chemistry, 2025)
Formin1 (FMN1), a member of the non-diaphanous formin family, is essential for development and neuronal function. Unlike diaphanous-related formins, FMN1 is not subject to canonical autoinhibition through the DID and DAD domains, nor is it activated by Rho GTPase binding. Recent studies suggest that formins also play roles in the nucleus, influencing DNA damage response and transcriptional regulation. However, the mechanisms regulating formins particularly non-diaphanous ones like FMN1 remain poorly understood. Our previous research identified the interaction between FMN1 and formin-binding protein 4 (FNBP4), prompting further investigation into its functional role in regulating actin dynamics. Results reveal that FNBP4 inhibits FMN1-mediated actin assembly in vitro. It is shown that FNBP4 prevents FMN1 from displacing the capping protein CapZ at the growing barbed end of actin filaments. Additionally, FNBP4 inhibits FMN1’s bundling activity in a concentration-dependent manner. Further analysis indicates that FNBP4 interacts with the FH1 domain and the interdomain connector between the FH1 and FH2 domains, creating spatial constraints on the FH2 domain. We propose that FNBP4 acts as a stationary inhibitor of FMN1. In addition, our subcellular localization studies revealed that FNBP4 is exclusively nuclear, supported by the identification of a monopartite nuclear localization signal within its sequence, suggesting a potential role in regulating nuclear actin dynamics. This study provides new insights into the regulatory role of FNBP4 in modulating FMN1-mediated actin dynamics, shedding light on regulatory mechanisms specific to non-diaphanous formins.